Glyphosate Resistance in Weed Biotypes (Paspalumpaniculatum L.) in the Costa Rican Caribbean Region - Ramírez-Muñoz, Fernando (2016)
In order to determine the level of resistance , the growth response to increasing doses of glyphosate herbicide in biotypes of Paspalumpaniculatum (Poaceae) weed was studied in a Tambor de Alajuela greenhouse during the years 2012 and 2013. The Paspalum biotypes plants came from hearts of palm (pejibaye), conventional and organic banana farms at the Province of Limon, and from roadsides in Heredia and Guanacaste Provinces of Costa Rica. Plants were sprayed with increasing doses of glyphosate, harvested and their fresh weight was measured 21 days after treatment. In farms of conventional production of pejibaye and banana with over 12 years of applying glyphosate as a unique method of weed control, we found three (R) glyphosate-resistant biotypes, they need from 2.0 to 8.3 times more herbicide to suffer a reduction of 50% growth with respect to susceptible biotypes (S). S biotypes came from an organic banana farm and the roadsides, where the use of glyphosate was null or minimum.